2013
DOI: 10.1111/jan.12233
|View full text |Cite
|
Sign up to set email alerts
|

The importance of multidisciplinary teamwork and team climate for relational coordination among teams delivering care to older patients

Abstract: AimTo identify predictors of relational coordination among professionals delivering care to older patients.BackgroundRelational coordination is known to enhance quality of care in hospitals. The underlying mechanisms, however, remain poorly understood.DesignThis cross-sectional study was part of a larger evaluation study examining the opportunity to prevent loss of function in older patients due to hospitalization in the Netherlands.MethodsThis study was performed in spring 2010 among team members delivering c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 46 publications
(74 reference statements)
0
51
1
Order By: Relevance
“…This may reflect physicians typically having a central, coordinating role in inter-professional teams in specialized health-care settings in Norway. However, this result is contrary to that of Hartgerink et al [23]; they found that being a physician was associated with lower perceived team communication and relational ties. The authors explained this negative association as the result of medical specialists often making their treatment decisions independently of others—and consequently not interacting frequently with other team members.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This may reflect physicians typically having a central, coordinating role in inter-professional teams in specialized health-care settings in Norway. However, this result is contrary to that of Hartgerink et al [23]; they found that being a physician was associated with lower perceived team communication and relational ties. The authors explained this negative association as the result of medical specialists often making their treatment decisions independently of others—and consequently not interacting frequently with other team members.…”
Section: Discussioncontrasting
confidence: 99%
“…One explanation for this finding may be that women tend to be more oriented towards interpersonal relations and social interactions—and therefore provide higher communication sub-scale scores—than men [42]. Research has shown that nurses were more positive towards collaborating in a team environment than physicians, who traditionally learn to make more independent decisions [2343]. Another study found a positive relationship between women and the degree of relational coordination [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well documented in the field of health sociology, that healthcare professionals' need to maintain professional identities hinders interdisciplinary collaboration. 26 Hartgerink et al 27 found that physicians were less open to interdisciplinary collaboration compared to nurses. Even within the medical profession, doctors have been found to share more information with colleagues from the same discipline.…”
Section: Discussionmentioning
confidence: 99%